الأنشطة اللغوية العربية فى معهد طوالب غونونج نحو القضايا والتحليل - Saputra, Indra; Sa’adiyah, Hurriyatus (Institut Darul Quran Payakumbuh, 2021)
In this paper, the writer discusses the implementation of Arabic language activities at Tawalib Islamic Boarding School in Gunung Padang Panjang and analyzes the activities. This paper used a qualitative descriptive method. The results of the author's analysis based on the implementation of Arabic-language activities at this Islamic boarding school are in the form of 1. Practicing conversation which was held twice a week, 2. Presenting new vocabulary every day, and practicing speech in Arabic language. The difficulties found for students in learning Arabic at this school were understanding Arabic subject matter. It was was due to the lack of supporting media in learning. So that, the students became easily bored. as the solution, the writer suggests Tawalib Islamic Boarding School to complete the learning media.